2018
DOI: 10.1007/s11701-018-0813-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of synchronous robotic surgery for colorectal cancer with liver metastases

Abstract: Timing of resection and treatment of colorectal cancer (CRC) with liver metastases varies based on patient characteristics and center protocols. Concerns of increased morbidity and mortality (M&M) related to anesthetic time and blood loss have limited widespread adaptation of synchronous colorectal and liver resections. Furthermore, technical challenges have made minimally invasive synchronous resections less common. We present our series of synchronous robotic surgery for CRC with liver metastases. Retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 7 publications
1
40
1
Order By: Relevance
“…Even the simultaneous minimally invasive resection of colorectal liver metastases and the primary tumor can be performed safely and effectively [6][7][8]. A recent meta-analysis showed that simultaneous minimally invasive resection of colorectal cancer and synchronous liver metastases caused significantly lower intra-operative blood loss and blood transfusion, faster recovery of intestinal function and diet, shorter length of stay, and lower rates of surgical complications in comparison to open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Even the simultaneous minimally invasive resection of colorectal liver metastases and the primary tumor can be performed safely and effectively [6][7][8]. A recent meta-analysis showed that simultaneous minimally invasive resection of colorectal cancer and synchronous liver metastases caused significantly lower intra-operative blood loss and blood transfusion, faster recovery of intestinal function and diet, shorter length of stay, and lower rates of surgical complications in comparison to open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative morbidity and mortality are acceptable, confirming the data reported by minimally invasive surgery. In the series of Dwyer et al [11] , an anastomotic leakage is described, and this event strongly impact postoperative course due to the necessity of reoperation, questioning the risk of performing the colorectal anastomosis during synchronous resection.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion tax ranged from 0% to 12%. Complications and major morbidity included delayed wound healing after an abdominal perineal resection (APR) and a delayed rectal anastomotic failure after ileostomy reversal in synchronous resection [11] , 1 postoperative bile leak, 2 heart failure [9] . 90 days mortality was 0%.…”
Section: Crlm and Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-four simultaneous resections of the primary tumor and liver metastases were included. In these cases, RS added additional safety and effectiveness in the management of multiple metastases, improving shortterm outcomes such as EBL, bowel function return time and LOS, with the exception of operative time, reaching excellent R0 resection rates [34,55] . Even in selected cases requiring major liver resections, robotic surgery gained acceptable morbidity [56] .…”
Section: Colorectal Liver Metastasesmentioning
confidence: 99%